IMPLEMENTASI MODEL PEMBELAJARAN KOPERATIF DAN TRADISIONAL TERHADAP KETERAMPILAN SOSIAL SISWA DALAM MATA PELAJARAN PADA SMA KOTA PEKANBARU (Studi Koperative ) (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2015)
In the cooperative learning model teachers are expected to be able to create active,creative, impressive, and convenient learning atmosphere. The teaching and learning whichmay be employed to create students active learning in groups is cooperative learning. Amongcooperative learning techniques, jigsaw is more used by researchers in science education but it isunpopular in social science education. It has been proved that jigsaw can motivate students tostudy. In fact, cooperative learning is able to arouse the studentsâ attitude in History subject.Wardani (2002) stated that the jigsaw learning techniques is one of the techniques ofcooperative learning which enables to motivate active students to help each other to understandthe teaching materials to get high achievement.This study aimed to ascertain the differences of the cooperative learning towards studentsâattitude in History subject. The statistical test using Excel analysis for Windows was applied inthis study. In order to find out whether there was a difference, the Student t- test was used. Whenthere was no significant difference between the dependent variable in the pre-test, the ANCOVAwas used in the post-test. The results of the study showed that there was a difference betweencooperative learning using jigsaw and the traditional learning towards the studentsâ learningattitude in History subject.Key words: implementation, cooperative, traditional, attitude,